ANALYSIS OF PROJECT-BASED LEARNING (PJBL) IN THE MEDIA FOR TEACHING INDONESIAN LANGUAGE AND LITERATURE COURSE - Asih Andriyati Marliyah; Nurhayati Ganinda; Rini Lindawati; Wawan Hermawan (Indonesian language and literature education program Majapahit Islamic University, 2024)
This research aims to analyze the implementation of Project-Based Learning (PjBL) in the Media for Teaching Indonesia Language and Literature Course, focusing on the process, benefits, and challenges of PjBL implementation. The research method used in this study is qualitative descriptive research. The primary data of this research are the results of observations and documentation studies. The data sources for this research include the learning process of the course with practitioners, lesson plans, and student project results. The results of this study indicate that in the project-based learning process, there are three stages, namely 1) project launch, 2) guided inquiry and product creation, and 3) project conclusion. Meanwhile, the benefits of implementing PjBL are (1) practical skills, (2) collaboration and teamwork, (3) creativity and innovation, and (4) problem-solving. Lastly, there are challenges in implementing PjBL: (1) limited time, (2) resources and access to technology, (3) students' technological skills, and (4) subjective evaluation. Keywords: Learning, Project-Based Learning (PjBL), Media